2020
DOI: 10.1029/2020gl089477
|View full text |Cite
|
Sign up to set email alerts
|

East Asia Atmospheric River catalog: Annual Cycle, Transition Mechanism, and Precipitation

Abstract: An all‐season East Asia Atmospheric River (EA AR) catalog is constructed based on PanLu2.0. The annual cycle of EA AR exhibits eight stages, synchronizing with the seasonal‐to‐subseasonal variation of precipitation and their associated atmospheric steering. Particularly, extension of the western North Pacific subtropical high (WNPSH) to south China sea, due to the springtime east‐west thermal contrast, steers ARs over Southeast China (SEC), inducing spring precipitation. During the Asian summer monsoon season,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 42 publications
5
59
0
Order By: Relevance
“…Additionally, the latitudinal position of rain belts in the Mid‐summer is mainly confined in the south (20°N‐25°N) (Figure ), which is likely to result from the influence of tropical cyclones at this time (Cheng & Lu, 2020; Day et al., 2018; Pan & Lu, 2020). Rain belts then largely disappear in the Fall stage (Figure ) due to weaker moisture transports from the tropics.…”
Section: Weather Regimes Associated With the Monsoon Stages' Onset Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the latitudinal position of rain belts in the Mid‐summer is mainly confined in the south (20°N‐25°N) (Figure ), which is likely to result from the influence of tropical cyclones at this time (Cheng & Lu, 2020; Day et al., 2018; Pan & Lu, 2020). Rain belts then largely disappear in the Fall stage (Figure ) due to weaker moisture transports from the tropics.…”
Section: Weather Regimes Associated With the Monsoon Stages' Onset Inmentioning
confidence: 99%
“…As such, we employ a neural‐network‐based algorithm, the self‐organizing map (SOM), to classify the East Asian monsoon stages all year round. This method projects high‐dimensional data onto a low‐dimensional one and preserves the topological features (Kohonen, 2001), which has shown great potentials in classifying meteorological field patterns (Chiang et al., 2017; Dai et al., 2020; Johnson, 2013; Kong et al., 2017; Nishiyama et al., 2007; Pan & Lu, 2020). The results of the SOM‐based approach are then assessed with the monsoon onset dates documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have reported that AR frequently forms over the northwestern Pacific and causes heavy rainfall events in eastern China, Korea, and western Japan when making landfall. Unlike the U.S. west coast where AR is most frequent in winter, East Asian AR (hereafter, simply AR unless specified) is most pronounced in summer (Guan & Waliser, 2015; Kamae, Mei, & Xei et al., 2017; Kamae, Mei, Xie, Naoi, & Ueda, 2017; Mundhenk, Barnes, & Maloney, 2016; Pan & Lu, 2020). This contrasting seasonality is caused by the East Asian summer monsoon (EASM), which is characterized by the expansion of the western North Pacific subtropical high (WNPSH) and the associated monsoon rainfall (Chen et al., 2004; Wang & LinHo, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This sub‐seasonality implies that the nature of the EASM AR may vary from month to month and from region to region. Pan & Lu (2020) in fact showed that the subseasonal evolution of the EASM AR consists of four stages and that each stage is closely related with the subseasonal‐to‐seasonal variation of the atmospheric steering. Although such an objective classification is useful, only monthly evolution is considered below for a practical purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we refer to the participating algorithms in ARTMIP as AR “detection” algorithms (or ARDTs). Recently, various research groups have developed AR “tracking” algorithms for AR lifecycle tracking (Guan & Waliser, 2019; Rhoades, Jones, O'Brien, et al., 2020; Pan & Lu, 2019, 2020; Payne & Magnusdottir, 2014; Shearer et al., 2020; Xu et al., 2020b, 2020a; Zhou et al., 2018; Zhou & Kim, 2019). Comparison between AR tracking algorithms has been shown by previous studies.…”
Section: Introductionmentioning
confidence: 99%